Sacrifice, Session and Intercession:The End of Christ's Offering in Hebrews. (June 2020) - Moore, Nicholas J.
A growing number of scholars have argued that Christ's offering in Hebrews is not limited to the cross but extends into heaven; in recent work David Moffitt contends that Christ's heavenly, atoning offering is perpetual and coextensive with his intercession. This article calls this further step into question, by examining the function of Christ's heavenly session in Hebrews' construal of sacrificial process, and by exploring the nature of his heavenly intercession and its relation to his offering and enthronement. It argues that Christ's session is a hinge, marking an emphatic close to his sacrificial work for the forgiveness of sins, and inaugurating his royal reign and priestly prayer.